PENGGUNAAN METODE WATERFALL DALAM PERANCANGAN SISTEM INFORMASI PENJUALAN TRIFTING - Jered Imanuel Wanda; Emy L Tatuhey (ADISAM PUBLISHER, 2025)
Clothing is a basic human necessity that continues to evolve with changing trends and lifestyles. One of the emerging trends today is thrifting, which refers to the buying and selling of second-hand clothing, increasingly popular among teenagers. OneTrif is a thrifting clothing sales platform based in Jayapura, Papua, designed to provide easier access for the community to branded clothing at affordable prices. However, its management faces several challenges, such as manual sales processes, difficulties in stock management, and a lack of transparency in transaction recording. To address these issues, a thrifting sales information system has been developed using the Waterfall methodology, which includes requirement analysis, system design, implementation, testing, and maintenance phases. The system design is structured using context diagrams, hierarchical diagrams, overview diagrams, and Entity Relationship Diagram (ERD) to ensure a clear and efficient process flow. The results of this study are expected to provide an optimal solution for OneTrif in managing transactions, speeding up sales processes, and enhancing user experience in digital thrifting shopping